Aircraft Gust Alleviation Preview Control with a Discrete-Time LPV Model - Ryoichi Takase; Yoshiro Hamada; Takashi Shimomura (SICE Journal of Control, Measurement, and System Integration, 2018)
This paper deals with a gust alleviation (GA) system using gain-scheduled (GS) discrete-time preview control. The key points to improve control performance of this system are in both modeling accuracy of the linear parameter-varying (LPV) system with a small number of scheduling parameters and design of the advanced GS controller. In this study, a discrete-time LPV model of the aircraft with a small number of essential scheduling parameters is proposed through a series of approximations based on understanding of flight dynamics. A GS controller is designed with the extended linear matrix inequality (LMI) while constructing a smaller convex hull to the LPV model. The simulation result shows that the proposed control system effectively attenuates aircraft vertical acceleration in turbulence and it is robust against cruising speed changes.